IMPLEMENTASI APLIKASI PENYUSUNAN LAPORAN KEUANGAN DAN ANALISIS KINERJA ATAS TRANSAKSI KEUANGAN DI SMK NEGERI 11 BANDUNG - Kastaman Kastaman; Renny Sukawati; Fajri Ardiansyah; Teguh Dian Lolonta Bangun; Henokh Putri Sugiyarwi; Ni Putu Kanaya Putri Cahyani (Jurnal Abdimas Bina Bangsa, 2024)
POAC human resource management of the company's human resources to achieve goals. The success of an organisation depends on human and material resources. Finance is critical to business. MSMEs struggle with finances because they don't know where their capital, personal money, and sales go. MSME companies need good financial management. OJK reported financial literacy below 40% in 2019. Technology has evolved throughout history, many civilisations, governments, and countries have been affected by this development. Everyone wants to use and benefit from new inventions. Technology reached its peak in 2000 after rapid advancement. Information and communication technology is used 24/7 by everyone. Various ways are simplified by technology. Including communication, information, commerce, education, entertainment, and personal needs. Students are expected to be able to use applications well to succeed in life in this rapidly changing technological environment. BPS data in May 2022 shows SMK graduates have the highest unemployment rate in Indonesia. Of the 35 Regional Enterprise Service Agency schools in West Java, SMKN 11 Bandung is one of them. Therefore, financial application recording and reporting must be improved